Caractérisation phénotypique et génotypique de deux Lactobacillus isolés d’un fromage traditionnel frais type J’ben - DAHOU, Amine; HOMRANI, Abdelkader; BENSALEH, Farid; BEKADA, Ahmed; MEGHOUFEL, Naima (Afrique SCIENCE, 2016)
Abstract Phenotypic and genotypic characterization of two Lactobacilli isolated from a traditional cheese type J'ben The purpose of this study is to evaluate the diversity of lactobacilli of a terroir cheese, type J'ben made from the milk of goats of Arabia breed. The milk is produced on a holding of the Algerian steppe regions of NAAMA. Two lactobacilli of cheese samples, recovered from the exploitation, were isolated and analyzed using phenotypic and genotypic methods. On all isolated species, 04 isolates were selected after phenotypic characterization by classical microbiological techniques based on the search of a certain number of morphological, physiological and biochemical characters. The purified isolates were stored in MRS and glycerol mixture to a molecular characterization based on the amplification then sequencing of bacterial DNA. The isolation of bacterial DNA from purified culture of Lactobacillus was established by an amplification of the 16 S ribosomal DNA by specific universal primers prokaryotes with the Lactobacillus delbrueckii reference strain ATCC 11842 used as a positive witness. Sequencing of the 16S DNA of all isolates have been realized and two different species have been identified with a predominance of Lactobacillus delbrueckii and Lactobacillus brevis. The evaluation of technological properties of the recovered isolates such as the production of exo polysaccharides (EPS) and proteolytic activity was inconclusive.----------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------------Résumé: Le but de cette étude était d’évaluer la diversité des lactobacilles d’un fromage du terroir type J’ben fabriqué à partir de lait de chèvre de race Arabia produit d’une exploitation des régions steppiques algériennes de NAAMA. Deux lactobacilles ont été isolés des échantillons de fromage récupérés de l’exploitation et analysés à l’aide de méthodes phénotypiques et génotypiques .Sur toutes les espèces isolées ; 04 isolats ont été retenues après caractérisation phénotypique par les techniques classiques de microbiologie basées sur la recherche d’un certain nombre de caractères morphologiques , physiologiques et biochimiques. Les isolats purifiés ont été conservés dans un mélange MRS et glycérol en vue d’une caractérisation moléculaire basée sur l’amplification puis séquençage de l’ADN bactérien. L’isolement de l’ADN bactérien à partir de la culture purifiée de lactobacille a été établi par une amplification de l’ADN ribosomal 16 S par des amorces universelles spécifiques des procaryotes avec une souche de référence Lactobacillus delbrueckii ATTC 11842 utilisé comme témoin positif. Le séquençage de l’ADN 16S de tous les isolats a été réalisé et deux espèces différentes ont été identifiées avec une prédominance de Lactobacillus delbrueckii et Lactobacillus brevis. L’évaluation des propriétés technologiques des isolats récupérés telle que la production d’exo polysaccharides (EPS) et l’activité protéolytique s’est avérée concluante.
Keywords: Mots-clés : fromage du terroir type J’ben, lait de chèvre de race Arabia, caractérisation phénotypique et génotypique, Lactobacillus delbrueckii, Lactobacillus brevis.; Keywords : local cheese types J'ben, breed goat milk Arabia, phenotypic and genotypic characterization, Lactobacillus delbrueckii, Lactobacillus brevis.